Physical violence and property damage towards parents, committed by adult children with drug problems - Johnson, Björn (Journal of family violence, 2022)
Drug use has previously been identified as a risk factor for child-to-parent abuse. We examine how common it is for parents to be exposed to physical violence and property damage by adult children with drug problems, and whether such victimization varies based on factors related to the parents and the adult children, respectively. A self-report questionnaire on victimization was completed by 687 parents of adult children with drug problems. The data were collected via a postal questionnaire to members of the Parents Against Drugs association and a web-based questionnaire to persons recruited via social media, treatment centers and other associations for families of drug users. The proportion of parents who reported having been exposed to physical violence was 19% ever, 6% during the past year. The proportion who had been exposed to property damage was 40% ever, 10% during the past year. Exposure during the past year was higher among parents whose children were currently experiencing drug problems. Mental health problems in the children were associated with higher levels of parental victimization, particularly in the form of physical violence. Parental victimization was also associated with the children being younger and still living at home. Exposure to property damage was higher among parents of male children. Adult children’s drug problems are of significance for parental victimization; they do not however appear to constitute a major risk factor but rather one risk factor among several others. Exposure to physical violence is clearly related to the presence of mental health problems in the children.